2015
DOI: 10.1155/2015/486960
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of HIV-Associated Neurocognitive Disorders (HAND) in Northwestern Nigeria

Abstract: HIV-associated Neurocognitive Disorders (HAND) are common among HIV-positive individuals. This study explored the prevalence and correlates of HAND in Nigeria. 80 HIV-positive and 40 HIV-negative adults selected from Aminu Kano Teaching Hospital (AKTH) received comprehensive evaluations. A multidomain neuropsychological test (MDNPT) battery assessing 7 domains was administered to the participants and their performance was combined with measures of functional status to classify impairments into various grades o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 28 publications
1
44
2
1
Order By: Relevance
“…However, the prevalence of HAND in the current study was higher than a cross-sectional study done in Brazil (53%)(16), (53%)(4), in Botswana (38%)(8) Indonesia (51%)(26), Nigeria 30%(20), South Africa (25%) (27), South Asia (22.7%) (13) and in Ethiopia at Debre Markos North West (24.8%) (17), Dessie (36.4%) (18) and the Mekele referral hospital Northern Ethiopia 33.3% (21). The differences might be accounted to the neurovirulence strain differences and sociodemographic differences.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the prevalence of HAND in the current study was higher than a cross-sectional study done in Brazil (53%)(16), (53%)(4), in Botswana (38%)(8) Indonesia (51%)(26), Nigeria 30%(20), South Africa (25%) (27), South Asia (22.7%) (13) and in Ethiopia at Debre Markos North West (24.8%) (17), Dessie (36.4%) (18) and the Mekele referral hospital Northern Ethiopia 33.3% (21). The differences might be accounted to the neurovirulence strain differences and sociodemographic differences.…”
Section: Discussioncontrasting
confidence: 75%
“…Gender, education, marital status, current CD4 count and hospital stay were included in the model based on previous studies showing them to be consistent predictors for neurocognitive impairment. [25][26][27][28][29][30][31][32] The logistic regression model was statistically significant, χ2 (9) = 72.91. The model explained 35.0% (Nagelkerke R 2 ) of the variance in neurocognitive impairment status and correctly classified 75.8% of cases.…”
Section: Factors Associated With the Neurocognitive Impairment: A Mulmentioning
confidence: 91%
“…Since our study was a cross sectional in design, possibly a onetime assessment of CD4 counts and its association with HAND was inconclusive. A study in Nigeria by Yakasai et al 21 also reported a similar result in which HAND was found in 40% of the pre-ART group and 30% of the ART group. This finding signified that HAND is common in the present ART era and also implied that ART does not apparently prevent the development nor successfully treat HAND among PLHIV.…”
Section: Screening Of Handmentioning
confidence: 52%
“…https://dnd.or.kr In the Charter study the prevalence of HAND was 52% as assessed by detailed neurocognitive test battery. 11 Yakasai et al 21 also explored the prevalence of HAND in Nigeria by using a MDNPT battery combined with measures of functional status by using PAOFI and Karnofsky performance scale and reported HAND prevalence of 40% in ART naive and 30% in on ART subjects.…”
Section: Screening Of Handmentioning
confidence: 99%